Bison wallows effect on soil properties, vegetation composition and structure in a recently reintroduced area - Nolasco, Ana Laura; Siebe, Christina; Ceballos, Gerardo; List, Rurik (THERYA, 2022)
Bison are considered an ecologically keystone species of the North American grasslands because their activities influence ecosystem dynamics and interactions, particularly their wallowing behavior. In 2009, 23 bison were reintroduced within a 1,500 ha private native semi-arid grassland in Janos, Chihuahua. Our objective was to evaluate the effect of bison wallows on the composition and structure of the vegetation, on species composition of annual grasses, and soil properties. Soil and vegetation samples were taken from inside the wallows and were compared against the samples obtained outside the wallows from late August to early September. The percentage of plant cover and the height of the foliage were measured inside and outside the wallow. Soil cores were taken, and the presence of soluble salts, moisture retention capacity, percentage of clay, and concentration of nutrients was determined. The three associations preferred by bison for wallowing were toboso grassland, vine mesquite and annual grassland. Of the 27 species of grasses and forbs recorded in the three plant associations mostly used for wallowing, we found that 17 species were present inside and outside wallows. Five different species were found only inside wallows and another five, only outside of wallows. The annual grassland plants had a greater height outside the wallows. The toboso grassland association presented higher soil moisture, likely related to the higher percentage of clay, and the annual grassland presented the highest bulk density (BD) inside the wallows, which limited plant growth in this association. Soils in other associations did not show significant differences in BD among them, mainly due to their finer texture. No significant effect of the wallows on nutrient concentrations was recorded. The lack of significant differences related to bison activities could be related to the brief period since the herd was reintroduced to the site. These differences might become apparent over time with a larger herd. For this reason, we conclude that the current differences in the soil properties are mainly due to geomorphological processes. That is, at this stage after the reintroduction, the grasslands are responding to soil characteristics, and not to the activity of the bison.